Auditory Function Recovery In Sudden Sensorineural Hearing Loss: 3-Year Study - Bogdan Cavaleriu; Luminita Radulescu; Daniel Rusu; Costela Gegea; Corina Butnaru; Dan Martu (Romanian Society of Oral Rehabilitation, 2012)
Objectives: The goal of this study was to assess the post-therapeutic rehabilitation for a group of patients in order to evaluate the conventional treatment of sudden sensorineural hearing loss. Materials and methods: 45 patients diagnosed with sudden sensorineural hearing loss, where clinically examined. A careful examination is needed to exclude life threatening causes such as vascular events and malignant diseases. Conventional treatment that include corticosteroids, antiviral drugs, vasoactive and vitamins (B1, B6) was administered to patients. Results: Post-treatment rehabilitation degree varies. The greatest recovery of hearing has been shown when corticosteroids are started within the first 1-2 weeks after symptom onset. About 45% of patients show good recovery, usually in about 2 weeks. Patients in whom there is no change within 2 weeks are unlikely to show much recovery. Conclusions: In most cases the cause is not identified, although various infective, vascular, and immune causes have been proposed. It is recommended that patients with sudden sensorineural hearing loss with no clear underlying cause after investigation are treated with a short course of oral prednisolone started within 2 weeks after onset. There is much to learn about pathogenesis of sudden sensorineural hearing loss and more clinical trials are needed to establish evidence-based management.